2012
DOI: 10.1539/joh.12-0016-br
|View full text |Cite
|
Sign up to set email alerts
|

Measles among Healthcare Workers in a Teaching Hospital in Central Italy

Abstract: Four cases of measles infection in HCWs were identified; of the 72 HCWs tested for measles immunity, 50 reported a past history of measles, while 22 underwent serological screening, which showed that all were IgG positive except for one case, which was excluded from duty as recommended. Strict adherence to use of alcohol-based hand rub and rapid implementation of appropriate isolation precautions are essential but insufficient to prevent measles outbreaks in hospital settings. Vaccination is the only reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 9 publications
2
18
0
1
Order By: Relevance
“…Studies from most regions of the world have described proportions of healthcare personnel without measles IgG antibodies ranging from 0–46% (median 6.5%) [17, 18, 22, 4798] (Table 1). The proportion of healthcare personnel without measles IgG antibodies was lowest in Africa (median 1.8%, interquartile range 0.9%– 2.6%) and highest in Asia and the Western Pacific (median 10.3%, interquartile range 7.2%- 12.2%) and the Middle East (median 9.2%, interquartile range 4.6%- 13.4%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies from most regions of the world have described proportions of healthcare personnel without measles IgG antibodies ranging from 0–46% (median 6.5%) [17, 18, 22, 4798] (Table 1). The proportion of healthcare personnel without measles IgG antibodies was lowest in Africa (median 1.8%, interquartile range 0.9%– 2.6%) and highest in Asia and the Western Pacific (median 10.3%, interquartile range 7.2%- 12.2%) and the Middle East (median 9.2%, interquartile range 4.6%- 13.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Studies from Europe on measles seroprevalence of healthcare personnel published between 1994 and 2013 reported that a median of 6.0% (interquartile range 3.3%-14%) of healthcare personnel were seronegative to measles, including those who thought they had a history of measles disease and/or history of measles vaccination [22, 48–65]. These articles also found differences in seroprevalence based on age, with older personnel less likely to be seronegative [49, 5155].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…), psychological (stress etc.) deformation (Bi et al, 2008;Saha et al,2005;Clarke et al, 2002;Sun et al, 2012;Barbadoro et al, 2012;Uchiyama et al, 2013;Wang et al, 2014;Errico et al, 2013;Kişioğlu et al, 2002;Sveinsdóttir, Biering & Ramel, 2006) and they catch contagious diseases such as AIDS, hepatitis; skin diseases such as dermatitis; vascular diseases such as varicosis; and occupational diseases such as cancer due to the fact that their occupational environment safety is not ensured (Berton & Novi, 2012;Horsman & Sheeran, 1995;Bell, 1997).…”
mentioning
confidence: 99%